Homogeneity-dependent fracture behavior and instability mechanism of composite coal-rock: Insights from three-point bending tests - Yue, Weitao; Wang, Enyuan; Feng, Xiaojun; Tan, Tingjiang; Zhang, Li; Chen, Dong; Zhang, Qiming; Ding, Zeng (International journal of mining science and technology, 2025)
To investigate the instability mechanisms of heterogeneous geological structures in goaf area roofs, three-point bending tests (TPBT) and numerical simulations are performed on composite coal-rock (CCR). Acoustic emission (AE) monitoring is employed to analyze key parameters, establishing a multi-parameter quantitative system for CCR fracture processes. The impact of lithological homogeneity on fracture evolution and energy migration is examined. Results show that CCR exhibits a three-stage mechanical response: weak contact, strong contact, and post-peak stages, each with distinct crack evolution patterns. A positive correlation is found between lithological homogeneity and tensile crack proportion. No significant correlation is observed between AE average frequency (AF) and AE counts across different lithological CCR; however, peak frequency (PF) displays clear lithology-dependent characteristics. The regulatory effect of the rock homogeneity coefficient (φ) on crack derivation mechanisms is quantified, yielding mathematical relationships between fracture strength (f), crack propagation path angle (β), crack fractal dimension (D), and φ. The study highlights how different fracture modes alter energy migration pathways, confirming the coupling effect of grain distribution on mechanical response and crack propagation, and the influence of parameter φ on critical energy release zones. These findings offer new insights into CCR failure mechanisms for mining safety.